Beat the devils - Weiss, Josh (New York ; Boston : Grand Central Publishing, 2022)
"USA, 1958. President Joseph McCarthy sits in the White House, elected on a wave of populist xenophobia and barely-concealed anti-Semitism. The country is in the firm grip of McCarthy's Hueys, a secret police force evolved from the House of Unamerican Activities Committee. Hollywood's sparkling vision of the American dream has been suppressed; its remaining talents forced to turn out endless anti-communist propaganda. LAPD detective Morris Baker-a Holocaust survivor who drowns his fractured memories of the unspeakable in schnapps and work-is called to the scene of a horrific double-homicide. The victims are John Huston, a once-promising but now forgotten film director, and an up-and-coming young journalist named Walter Cronkite. Clutched in the hand of one of the dead men is a cryptic note containing the phrase "beat the devils" followed by a single name: Baker. Did the two men die in a murder-suicide, as the Hueys are quick to conclude, or were they murdered in a coverup designed to protect-or even set in motion-a secret plot connected to Baker's past? In a country where terror grows stronger by the day, and paranoia rises unchecked, Baker is determined to find justice for two men who raised their voices in a time when free speech comes at the ultimate cost. In the course of his investigation, Baker stumbles into a conspiracy that reaches deep into the halls of power and uncovers a secret that could destroy the City of Angels-and the American ideal itself"--
Keywords: Thrillers (Fiction); Detective and mystery fiction; Alternative histories (Fiction); Novels